Pembinaan Prestasi Bulutangkis PB. Bina Mutiara Kabupaten Brebes Tahun 2020 (Indonesian Journal for Physical Education and Sport, 2021)
The purpose of this study was to determine the process of coaching and training program for badminton athletes at Bina Mutiara Brebes. The research method used descriptive qualitative. the research location was at Bina Mutiara Badminton Brebes Regency with data source in the form 1) person including: administrators, coaches, and athletes, 2) place: badminton court. Data collection technique using observation, interview and documentation. data analysis using reduction, data presentation, and conclusions. the reults showed: 1) financial support was not going well, 2) structured organization but less active in carrying out its duties, 3) performance development at Bina Mutiara Club had not been able to complete at the district level, 4) infrastructure was good, 5) the training technique at Bina Mutiara Club seen with the average value of basic skills test such as standing attitude in the very good category of 65,62% holding the racket by 46,78%, serving category by 40,62%, lob category by 46,87%, smash category by 56,25%, drop shot category by 40,62%, drive category by 34,37%, netting category by 40,62% and the footsteps category by 50%. The conclusion of this research was the process of coaching at Bina Mutiara Club was good enough for instratucture and training technique, but for financial support, organization, and performance development were still lacking and needed to be improve.